High-entropy MAX-phase ceramic material as well as preparation method and application thereof

By using high-entropy MAX phase ceramic materials, the "high entropy effect" of multi-main elements makes MAX phase ceramics "high entropy" at the M position, solving the limitations of existing MAX phase materials in impedance matching and polarization loss types, and significantly improving the electromagnetic wave absorption performance.

CN119797923APending Publication Date: 2025-04-11HEFEI INNOVATION RES INST BEIHANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411842449.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The limitations of existing MAX phase materials in impedance matching and polarization loss types hinder further improvements in electromagnetic wave absorption performance.

Method used

A high-entropy MAX phase ceramic material is used, with the molecular formula of M2AlC, where M is selected from at least four of Ti, Zr, Hf, Nb, Ta, and V, and is prepared by vacuum hot pressing sintering method, and the MAX phase ceramic is "high-entropy" at the M position using the "high-entropy effect" of the multi-main element.

Benefits of technology

The electromagnetic wave absorption performance is significantly improved, especially in impedance matching and polarization loss types, achieving better absorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797923A_ABST
    Figure CN119797923A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy MAX phase ceramic material and a preparation method and application thereof, the molecular formula of the high-entropy MAX phase ceramic material is M2AlC, and M is selected from at least four of Ti, Zr, Hf, Nb, Ta and V. The high-entropy MAX phase ceramic material is prepared by a vacuum hot pressing sintering method, on one hand, transfer of temperature and pressure is facilitated under vacuum hot pressing, the temperature and the pressure are more uniform and sufficient, the tissue structure of the prepared high-entropy MAX phase ceramic material sample is more compact and uniform, and the obtained performance is more excellent; and 2, oxidation during sample preparation can be prevented, and pollution of impurities to the sample is reduced, so that the sample with higher purity can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic non-metallic conductive ceramics, and in particular to a high-entropy MAX phase ceramic material and a preparation method and application thereof. Background Art

[0002] The rapid development of modern communication technology has provided great convenience for human daily life, but its harm to human health and the natural environment is also becoming increasingly serious. Therefore, it is very necessary to study new microwave absorbing materials suitable for complex electromagnetic environments. As a new type of electromagnetic wave absorbing material, it needs to not only effectively reduce the pollution of electromagnetic waves, but also have important application value in radar stealth materials, microwave darkrooms, electromagnetic wave attenuation devices, wearable devices, etc. Therefore, in many fields such as electromagnetic radiation, electromagnetic interference, anti-electromagnetic leakage and military stealth, electromagnetic microwave absorbing materials are very important materials. MAX phase is a type of ternary carbide and / or nitride with a hexagonal layered structure, M is a transition metal element, A is mainly a IIIA~VA group element, and X is a C and / or N element. MAX phase material can also be called metal ceramic or conductive ceramic, which is composed of layered transition metal carbonitride and A atomic layers stacked on each other. This unique structure makes it not only have the excellent properties of traditional ceramics, but also have the characteristics of metal materials. MAX phase materials usually have excellent electrical / thermal conductivity and high dielectric loss, so they are considered to be ideal electromagnetic interference shielding materials in harsh environments. Therefore, in the field of electromagnetic wave absorption, a large number of scholars have explored the absorbing ability of MAX phases, but their limitations in impedance matching and polarization loss types still hinder further performance improvements. Summary of the invention

[0003] In order to improve the above technical problems, the present invention provides a high entropy MAX phase ceramic material, whose molecular formula is M2AlC, wherein M is selected from at least four of Ti, Zr, Hf, Nb, Ta, and V.

[0004] According to an embodiment of the present invention, the M is a mixture of Ti, Zr, Hf, Nb and V.

[0005] According to an embodiment of the present invention, the high entropy MAX phase material is (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC.

[0006] The present invention also provides a method for preparing the high entropy MAX phase ceramic material, the method comprising:

[0007] At least four M-containing compounds are mixed with Al powder and C powder, and the obtained mixed powder is pressed into shape and then hot-pressed and sintered to prepare a high-entropy MAX phase ceramic material.

[0008] According to an embodiment of the present invention, the M-containing compound is selected from at least one of Ti powder, ZrC powder, HfC powder, V powder or Nb powder.

[0009] According to an embodiment of the present invention, the molar ratio of the total molar content of at least four M-containing compounds to the Al powder and the C powder is 2:(1.1-1.5):0.2.

[0010] According to an embodiment of the present invention, the particle size of the mixed powder is 10-20 μm, for example 15 μm.

[0011] According to an embodiment of the present invention, during the compression molding process, the applied pressure is 10-20 MPa, for example, 15 MPa, and the holding time is 3-8 min, for example, 5 min.

[0012] According to an embodiment of the present invention, the pressure of hot pressing sintering is 20-50MPa, for example, 30MPa, the temperature of hot pressing sintering is 1450-1600°C, for example, 1450°C, 1500°C or 1600°C, and the heating rate of hot pressing sintering is 1-10°C·min -1 The hot pressing sintering time is 2-5 hours, for example, 5 hours. Preferably, the hot pressing sintering is performed in an inert atmosphere; for example, the inert atmosphere is nitrogen, argon, etc.

[0013] Specifically, the hot pressing sintering process is as follows: the pressure is 30 MPa, first at 10 ° C min -1 From room temperature to 1200℃, then at 2℃·min -1 The heating rate was from 1200°C to 1600°C and kept at this temperature for 5h.

[0014] According to an embodiment of the present invention, the method is specifically:

[0015] The mixed powder of the ball-milled Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder was pressed into a shape and then hot-pressed and sintered to prepare (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC ceramic material.

[0016] According to an embodiment of the present invention, the molar ratio of the Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder is 0.4:0.4:0.4:0.4:0.4:1.2:0.2.

[0017] According to an embodiment of the present invention, the mixed powder is ball-milled in a planetary ball mill, with a ball-to-material ratio of 10-20:1, for example, 15:1, a rotation speed of 300-600 r / min, for example, 400 r / min, and a time of 12-30 h, for example, 24 h; the grinding medium used is silicon nitride balls, and the diameter of the silicon nitride balls is 6-15 mm, for example, 10 mm; and the ball milling medium is acetone.

[0018] As an exemplary embodiment of the present invention, the preparation method of the high entropy MAX phase ceramic material is as follows:

[0019] Step S1: Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder are weighed and mixed according to a certain proportion, and the obtained powders are dispersed in a polyethylene plastic bottle filled with acetone, and silicon nitride is used as a grinding medium. After sealing, the powders are ball-milled using a planetary ball mill;

[0020] Step S2: drying the composite powder obtained in step S1, and then sieving it with a sieve;

[0021] Step S3: After the powder obtained in step S2 is pressed into tablets, hot-pressed and sintered, the temperature is naturally lowered after being kept at a temperature for a period of time to obtain a high-entropy MAX phase ceramic material.

[0022] Specifically, in step S2, a standard 92A type vibrating sieve machine is used for sieving, and the particle size of the powder after sieving is 10-20 μm, for example, 15 μm.

[0023] Preferably, the size of the sieve used for sieving is 200 mesh. For the powder particles that cannot pass through the sieve, the powder is ground into powder using a mortar and then passed through the sieve to make the powder size 15 μm.

[0024] Preferably, in step S2, a rotary evaporator is used for drying, the drying temperature is 40-80°C, such as 60°C, and the drying time is 1-5h, such as 3h.

[0025] Preferably, in step S3, the pressure applied during the pressing process is 10-20 MPa, for example, 15 MPa, and the holding time is 3-8 min, for example, 5 min.

[0026] The present invention also provides the application of the high entropy MAX phase ceramic material in radar stealth materials, microwave darkrooms or electromagnetic wave attenuation devices.

[0027] Beneficial effects of the present invention:

[0028] The present invention uses a vacuum hot pressing sintering method to prepare high-entropy MAX phase ceramic materials. First, vacuum hot pressing is conducive to the transmission of temperature and pressure, and will also make the temperature and pressure more uniform and sufficient, so that the prepared high-entropy MAX phase ceramic material sample has a denser and more uniform organizational structure, and the obtained performance will also be better; second, it can prevent oxidation from occurring during sample preparation and reduce the contamination of the sample by impurities, thereby preparing samples with higher purity.

[0029] The present invention adopts a vacuum hot pressing sintering method to prepare high-entropy MAX phase ceramic materials, solid-dissolves four or more transition metal elements at the M position of the MAX phase for sintering, and utilizes the "high entropy effect" of multiple principal elements to make the MAX phase ceramic ceramic "high entropy" at the M position, thereby obtaining more excellent electromagnetic wave absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of Example 1.

[0031] Figure 2 is the SEM image of Comparative Example 1.

[0032] Figure 3 This is the SEM image of Comparative Example 2. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0034] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0035] Test Method

[0036] Scanning electron microscope (SEM) analysis: Use a focused high-energy electron beam to scan the surface, stimulate the sample surface to generate physical information such as secondary electrons and backscattered electrons, and collect this information to characterize the sample's microscopic morphology. Analyze the powder morphology, size, distribution, etc. of the MAX phase sample. The test equipment is the Thermo Fisher Quattro S.

[0037] Vector network analyzer (VNA) analysis: The coaxial transmission reflection method was used to test and evaluate the wave absorption performance of the samples obtained from the experiment. The test equipment is the American Agilent E5071c vector network analyzer, the test frequency range is 1-18GHz, and the step length is 0.01GHz. The preparation process of the test sample is: the powder of the sample to be tested is mixed evenly with paraffin in a certain mass ratio, heated to 80℃, poured into the mold, and pressed into a coaxial ring sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of 2.00mm.

[0038] Example 1

[0039] A method for preparing a high entropy MAX phase ceramic material comprises the following steps:

[0040] Ball milling steps: Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder are ball milled in a molar ratio of 0.4:0.4:0.4:0.4:0.4:1.2:0.2. The ball milling process is: ball-to-material ratio is 15:1, the rotation speed is 400r / min, the time is 24h, and the ball milling medium is 10mm silicon nitride ball.

[0041] Drying step: Dry the mixed powder using a rotary evaporator under vacuum at 60 °C for 3 h.

[0042] Screening step: Use a standard 92A vibrating screener with a 200-mesh screen. The particle size of the powder after screening is 15 μm.

[0043] Sintering steps: the mixed powder is pressed into a sheet and placed in a corundum crucible for sintering in a vacuum hot-pressing sintering furnace. The pressure applied during the pressing process is 15 MPa, and the pressure holding time is 5 min. The sintering method is as follows: the sintering furnace is evacuated to below 20 Pa at room temperature, and the nitrogen is pressurized to 30 MPa. The temperature is raised from room temperature to 1200 ° C at a rate of 10 ° C / min, and then heated at 2 ° C·min. -1 The heating rate was increased from 1200℃ to 1600℃ and kept at this temperature for 5h. After the end of the heat preservation, the pressure and temperature were immediately reduced, and the sample was cooled with the furnace. Finally, (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC ceramic material.

[0044] According to the analysis and test of the vector network analyzer (VNA), the best minimum reflection loss (RLmin) of the sample at 4.16GHz (thickness 4.1mm) is -45.54dB, and the best effective absorption bandwidth at 10.32~13.20GHz (thickness 1.8mm) is 2.88GHz.

[0045] Figure 1 This is the SEM image of Example 1. It can be seen from the figure that the sample has an obvious layered structure, there is no gap between the layers, the layers are thick and uniform, there is no obvious defect appearance, the structure is complete, and there is no fracture disorder.

[0046] Comparative Example 1

[0047] A method for preparing a high entropy MAX phase ceramic material comprises the steps of:

[0048] Ball milling steps: Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder are ball milled in a molar ratio of 0.4:0.4:0.4:0.4:0.4:1.2:0.2. The ball milling process is: ball-to-material ratio is 15:1, the rotation speed is 400r / min, the time is 24h, and the ball milling medium is 10mm silicon nitride ball.

[0049] Drying step: Dry the mixed powder using a rotary evaporator under vacuum at 60 °C for 3 h.

[0050] Screening step: Use a standard 92A vibrating screener with a 200-mesh screen. The particle size of the powder after screening is 15 μm.

[0051] Sintering steps: the mixed powder is pressed into a sheet and placed in a corundum crucible for sintering in a vacuum hot-pressing sintering furnace. The pressure applied during the pressing process is 15 MPa, and the pressure holding time is 5 min. The sintering method is as follows: the sintering furnace is evacuated to below 20 Pa at room temperature, and the nitrogen is pressurized to 30 MPa. The temperature is raised from room temperature to 1200 ° C at a rate of 10 ° C / min, and then heated at 2 ° C·min. -1 The heating rate was increased from 1200℃ to 1400℃, and the temperature was kept for 5h. After the temperature was kept, the pressure and temperature were immediately reduced. The sample was cooled with the furnace, and finally (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC ceramic material.

[0052] According to the analysis and test of the vector network analyzer (VNA), the best minimum reflection loss (RLmin) of the sample at 4.56GHz (thickness 2.4mm) is -36.68dB, and the best effective absorption bandwidth at 14.88~18.00GHz (thickness 0.8mm) is 3.12GHz.

[0053] Figure 2 This is the SEM image of comparative example 1. It can be seen from the figure that there is an obvious layered structure, but the structure is relatively incomplete and the surface is covered with many impurities.

[0054] Comparative Example 2

[0055] A method for preparing a high entropy MAX phase ceramic material comprises the steps of:

[0056] Ball milling steps: Ti powder, ZrC powder, HfC powder, V powder, Nb powder, Al powder and C powder are ball milled in a molar ratio of 0.4:0.4:0.4:0.4:0.4:1:0.2. The ball milling process is: ball-to-material ratio is 15:1, the rotation speed is 400r / min, the time is 24h, and the ball milling medium is 10mm silicon nitride ball.

[0057] Drying step: Dry the mixed powder using a rotary evaporator under vacuum at 60 °C for 3 h.

[0058] Screening step: Use a standard 92A vibrating screener with a 200-mesh screen. The particle size of the powder after screening is 15 μm.

[0059] Sintering steps: the mixed powder is pressed into a sheet and placed in a corundum crucible for sintering in a vacuum hot-pressing sintering furnace. The pressure applied during the pressing process is 15 MPa, and the pressure holding time is 5 min. The sintering method is as follows: the sintering furnace is evacuated to below 20 Pa at room temperature, and the nitrogen is pressurized to 30 MPa. The temperature is raised from room temperature to 1200 ° C at a rate of 10 ° C / min, and then heated at 2 ° C·min. -1 The heating rate was increased from 1200℃ to 1600℃, and the temperature was kept for 5h. After the temperature was kept, the pressure and temperature were immediately reduced. The sample was cooled with the furnace, and finally (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC ceramic material.

[0060] According to the analysis and test of the vector network analyzer (VNA), the best minimum reflection loss (RLmin) of the sample at 18.00GHz (thickness 1.5mm) is -23.74dB, and the best effective absorption bandwidth at 15.60~18.00GHz (thickness 1.6mm) is 2.40GHz.

[0061] Figure 3 This is the SEM image of Comparative Example 2. From the figure, it can be seen that there is a less obvious layered structure and the impurity particles are also relatively obvious.

[0062] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high entropy MAX phase ceramic material, characterized in that: Its molecular formula is M2AlC, wherein M is selected from at least four of Ti, Zr, Hf, Nb, Ta, and V.

2. The ceramic material according to claim 1, characterized in that The M is a mixture of Ti, Zr, Hf, Nb and V; The high entropy MAX phase material is (Ti 0.2 Zr 0.2 Hf 0.2 V 0.2 Nb 0.2 )2AlC.

3. A method for preparing the ceramic material according to claim 1 or 2, characterized in that: The method comprises: At least four M-containing compounds are mixed with Al powder and C powder, and the obtained mixed powder is pressed into shape and then hot-pressed and sintered to prepare a high-entropy MAX phase ceramic material.

4. The method according to claim 3, characterized in that: The M-containing compound is selected from at least one of Ti powder, ZrC powder, HfC powder, V powder or Nb powder.

5. The method according to claim 3, characterized in that: The molar ratio of the total molar content of at least four M-containing compounds to the Al powder and the C powder is 2:(1.1-1.5):0.

2.

6. The method according to claim 3, characterized in that The particle size of the mixed powder is 10-20 μm.

7. The method according to claim 3, characterized in that During the pressing process, the applied pressure is 10-20MPa and the holding time is 3-8min.

8. The method according to claim 3, characterized in that The pressure of hot pressing sintering is 20-50MPa, the temperature of hot pressing sintering is 1450-1600℃, and the heating rate of hot pressing sintering is 1-10℃·min -1 The hot pressing sintering time is 2-5h.

9. The method according to claim 3, characterized in that: The mixed powder is ball-milled in a planetary ball mill with a ball-to-material ratio of 10-20:1, a rotation speed of 300-600 r / min, and a time of 12-30 h; the grinding medium used is silicon nitride balls with a diameter of 6-15 mm, and the ball milling medium is acetone.

10. Use of the ceramic material according to claim 1 or 2 in radar stealth materials, microwave darkrooms, electromagnetic wave attenuation devices or wearable devices.

Citation Information

Cited By

  • MAX-phase high-temperature self-lubricating ceramic material and preparation method thereof

    CN121159279A